Scan speed affects quantitative optical coherence tomography angiography vascular metrics - Vidal Oliver, Lourdes; Herzig de Almeida, Elisa; Spissinger, Sabrina; Dolz-Marco, Rosa; Finger, Robert P. (Scientific reports, 2024)
Optical coherence tomography angiography (OCTA) offers the possibility of obtaining objective quantification of retinal vasculature, with increasing utility as biomarkers for both systemic and ocular diseases. However, the differences between different manufacturers and scan settings are still an important limitation, as many parameters could affect vessel quantification. Here we aim to study the influence of scan speed on quantitative vascular parameters using OCTA. 57 eyes in good retinal health received two consecutive 20 × 20° macular OCTA scans using SPECTRALIS SHIFT at different scan speeds: 85 and 125 kHz. Vessel density (VD) and vessel length density (VLD) in both the superficial (SVP) and deep vascular plexus (DVP), duration of the scan and Q-value were compared between scanning speeds. OCTA images taken at 85 kHz showed significantly higher VD and VLD values (% reduction in SVP: VD -4.03% to -5.8%, VLD − 4.96% to -6.07%; in DVP: VD -3.35% to -6.58%, VLD − 3.60% to -6.66%). At 125 kHz, acquisition time was reduced by 22%, but Q-values were lower (34.1 vs. 35.6). Thus, while higher A-scan rates reduce acquisition time, they lower VD and VLD in both plexus. Further studies in eyes with pathology are needed to better understand the magnitude of these changes.